Vitamin D Status and Associations With Risk Factors for Cardiovascular Disease and Diabetes in Children Enrolled in a Medical Weight Management Program. (August 2014) - Hanson, Corrine; Anderson-Berry, Ann; Hoskins, Shelby; Lyden, Elizabeth; Bilek, Laura; Dolphens, Tamara; Hartmann, Krystal; Hawkins, Mary Jane; Fernandez, Cristina
Background . Studies of vitamin D status have linked low 25(OH)D levels with biomarkers of cardiovascular disease and diabetes. Obese children and adolescents are at greater risk of vitamin D deficiency as vitamin D is thought to be sequestered in adipose tissue. The objective of this analysis was to examine the associations between 25(OH)D status and risk factors for cardiovascular disease and diabetes in a population of overweight and obese children enrolled in a medical management program. Materials and Methods . A retrospective chart review was conducted of 161 children enrolled in a medical weight management program. Pearson correlation coefficient were used to evaluate associations of biochemical measurements and 25(OH)D status. Multiple regression was used to evaluate 25(OH)D levels as a predictor of risk factors for cardiovascular disease and diabetes. Results . The mean body mass index (BMI) of the population was 34 kg/m 2, mean 25(OH)D levels were 21.8 ng/mL. White subjects had significantly higher 25(OH)D levels than non-whites (24.1 vs 19.2, P = .004). 25(OH)D levels were inversely related to BMI ( r = −0.21, P = .03) and waist circumference ( r = −0.23, P = .02). After adjustment for BMI and age, 25(OH)D was significantly associated with total cholesterol ( P = .0003), triglycerides ( P = .0007), homeostasis model assessment–estimated insulin resistance (HOMA-IR; P = .005) and insulin ( P = .0003). The decrease in each unit of cholesterol, triglycerides, and insulin for each 1% increase in log transformed 25(OH)D were 0.3, 0.65, and 0.1, 1 respectively. Each 1% increase in 25(OH)D levels was associated with a 0.05% decrease in HOMA-IR values. Conclusion . Vitamin D status was associated with risk factors for diabetes and cardiovascular disease in an obese pediatric population.